Genetic Variation Analysis of Mold (Magnaporthe oryzae B.Couch) Using Random Amplified Polymorphic DNA - Ajeng Kusumaningtyas Pramono; Budi Setiadi Daryono (Universitas Gadjah Mada, 2012)
Magnaporthe oryzae B.Couch is a host-specific fungi, certain strain only infect certain host plant species. Genetic variety among M. oryzae isolates was explained by dendogram which was constructed using similarity data of Random Amplified Polymorphic DNA (RAPD). Dendogram construction was achieved by computer software, Numerical Taxonomy System (NTSYS). The aim of the research were to study the genetic variation among M. Oryzae using RAPD and to construct a dendogram of genetic similarities among the ten isolates from green foxtail (Setaria viridis L.), finger millet (Eleusine coracana L.) and rice (Oryza sativa L.).RAPD was performed in 30 cycles using 5 primers (OPA-02, OPA-03, OPA-04, OPA-05, OPA-07). Polymorphism data was used to constructed dendogram using Dice index and Unweighted Pair Group Method with Arithmetic Mean (UPGMA) in NTSYS software. There were 68 polymorphism fragments from 74 amplified fragments.Three clusters were formed in the dendrogram, based on host pathotype: foxtail millet type, finger millet type and rice type. There were two subclusters in foxtail millet type based on mating type, MAT1-1 dan MAT1-2. Thus, RAPD could be used as a method for genetic variation analysis of Magnaporthe oryzae to show host-specific specificity.Key words: Magnaporthe oryzae, RAPD, mating type